From export boom to private debt bubble: a macroeconomic policy regime assessment of Canada's shifting growth regime - Theodore Klassen (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2024)
This paper examines the emergence of private debt-led growth in Canada since the Global Financial Crisis (GFC) by means of a growth regime and macroeconomic policy regime assessment. Examining each of the four business cycles in the 1983-2020 period, roughly encompassing the entirety of the neoliberal period, results demonstrate the emergence of a 'rising' weakly export-led growth regime in the early 1990s, a shift to a 'falling' weakly export-led regime by 2001, and a turn to a debt-led private demand regime since the GFC. The macroeconomic policy regime then identifies the structural changes and policy factors that have contributed to Canada's shifting growth regime. While price competitiveness played an important role in the first three cycles, it failed to re-establish an export-led regime in the post-GFC period due to decreased non-price competitiveness. Instead, the post-GFC combination of low real interest rates, which encouraged the accumulation of private debt and fiscal policy, which ex post did not address the negative financial balances of the household sector, supported the turn to private debt-led growth.
Keywords: E11; E12; E60; E65; F62; O51; 330; growth regimes; macroeconomic policy regime; financialization; private debt; post-Keynesian economics; Canada